Opposite nucleotide usage biases in different parts of the Corynebacterium diphtheriae spaC gene - Khrustalev, Vladislav Victorovich; Barkovsky, Eugene Victorovich; Kolodkina, Valentina Leonidovna; Khrustaleva, Tatyana Aleksandrovna (International journal of bioinformatics research and applications, 2015)
In this work we described a bacterial open reading frame with two different directions of nucleotide usage biases in its two parts. The level of GC-content in third codon positions (3GC) is equal to 40.17 ± 0.22% during the most of the length of Corynebacterium diphtheriae spaC gene. However, in the 3'-end of the same gene (from codon #1600 to codon #1873) 3GC level is equal to 64.61 ± 0.91%. Using original methodology ('VVTAK Sliding window' and 'VVTAK VarInvar') we approved that there is an ongoing mutational AT-pressure during the most of the length of spaC gene (up to codon #1599), and there is an ongoing mutational G-pressure in the 3′-end of spaC. Intragenic promoters predicted by three different methods may be the cause of the differences in preferable types of nucleotide mutations in spaC parts because of their autonomous transcription.